Covid-19 and the marginalisation of indigenous groups in Argentina. (April 2021) - Haas, Benjamin; Mönch, Tobias; Cervi, Lara
This article analyses how the Covid-19 pandemic has reinforced the stigmatisation and economic, social and cultural exclusion of indigenous groups in Argentina. Using the example of Qom/Toba in the northern province of Chaco and its capital Resistencia, the authors argue that the control of the pandemic regarding 'space' and 'movement' has considerably intensified practices of spatialised marginalisation of indigenous (non-white) persons, triggering also new strategies of self-empowerment and resistance. It shows how the 'governance of Covid-19' contributes to the perpetuation of power structures within the affective and geographical project of a 'White Argentina'.